Protection of a Taxpayer’s Rights and the Admissible Scope of Information Provided under Article 45 (1) of the National Tax Administration Act: Approving Commentary on the Judgment of the Polish Supreme Administrative Court of 4 May 2021 (III FSK 928/21, LEX no. 3181325) - Agnieszka Franczak (Studia Iuridica Lublinensia, 2023)
In the analyzed judgment, the Polish Supreme Administrative Court sets the limits on the tax authorities’ request for access to tax information pursuant to Article 45 (1) of the National Tax Administration Act. In the rationale for the judgment, the Court emphasized that this provision concerns a specific form of the authority’s action with respect to the collection, use, and processing of tax information. For this reason, the use of such a form of action is subject to certain restrictions. On the basis of this provision, tax authorities may not, in particular, take actions that are appropriate for formal proceedings (administrative, tax, or customs-fiscal). In the commentary, the justification of the Supreme Administrative Court was welcomed, developing the arguments supporting the main theses of the judgment and organizing the arguments presented in other judgments on this subject.